1986
DOI: 10.1159/000177201
|View full text |Cite
|
Sign up to set email alerts
|

Increased Platelet Aggregation during Alimentary Hyperlipemia in Normal and Hypertriglyceridemic Subjects

Abstract: The influence of 2 different fatty meals, rich in either saturated or polyunsaturated fatty acids, on platelet aggregation in 7 normolipemic subjects and in 10 patiens with phenotype IV hyperlipemia, was studied. 3 h after ingestion of a saturated- or polyunsaturated-fat-rich meal, plasma triglycerides were similarly increased in both groups. 5 h after ingestion of fat of either origin, the plasma triglyceride level in normal subjects returned almost to the fasting level, whereas in patients with hypertriglyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 19 publications
(25 reference statements)
0
18
1
Order By: Relevance
“…Platelet aggregation induced by ADP (24) and by collagen (25) was significantly increased in normolipemic subjects after fatty meals. Fuhrman et al (24) showed that platelets maintained their hypersensitivity to aggregation 5 h after meals, at a time when plasma TG levels had returned to normal.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Platelet aggregation induced by ADP (24) and by collagen (25) was significantly increased in normolipemic subjects after fatty meals. Fuhrman et al (24) showed that platelets maintained their hypersensitivity to aggregation 5 h after meals, at a time when plasma TG levels had returned to normal.…”
Section: Discussionmentioning
confidence: 90%
“…Platelet aggregation induced by ADP (24) and by collagen (25) was significantly increased in normolipemic subjects after fatty meals. Fuhrman et al (24) showed that platelets maintained their hypersensitivity to aggregation 5 h after meals, at a time when plasma TG levels had returned to normal. Chylomicron remnant particles enhanced activation of platelets stimulated with ADP and collagen (42), but native chylomicrons inhibited platelet function (43).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies suggest that individual saturated fatty acids differently affect platelet aggregation capacity (Fuhrman et al, 1986;Renaud et al, 1986). There are reports that chain length of fatty acids plays an important role in platelet aggregation and the inhibitory effect on platelet aggregation was increased with increase in chain length up to C 14 (Kitagawa et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Other pro-inflammatory and potentially atherogenic effects of postprandial lipoproteins include activation of leukocytes, promoting adhesion to the endothelium and invasion of the artery wall [12,40]. In addition, postprandial lipemia causes pro-thrombotic effects such as increasing coagulant factor VII [41] and plasminogen activator inhibitor type 1(PAI-1) activity [42] and increasing platelet activity [14,43] and aggregation [44].…”
Section: Postprandial Hyperlipidemia As a Risk Factor For Atherosclermentioning
confidence: 99%